Psychological Distress and Anxiety: A Case Study on Student-Athletes at University - Falah Tri Nur Afifah; Komarudin; Mochamad Yamin Saputra; Geraldi Novian (Universitas Negeri Semarang, 2025)
Student-athletes often find themselves juggling the demands of schoolwork and sports, which can create much pressure and lead to feelings of stress and anxiety. These difficulties do not just make it harder for them to do their best in class or on the field—they can also have a long-term impact on their mental health. This research seeks to explore how psychological distress is connected to anxiety among student-athletes. This study used a descriptive correlational quantitative method involving 61 student-athletes of the Faculty of Sport and Health Education, Universitas Pendidikan Indonesia. Data were collected using the Depression Anxiety Stress Scale (DASS-21) to measure psychological distress and the Sport Anxiety Scale (SAS-2) to measure sports anxiety through Google Forms. Data analysis used a normality test, Pearson correlation, and descriptive statistics with SPSS version 29. The results showed a strong and significant positive relationship between psychological distress and anxiety in student-athletes. Data showed 56.3% of student-athletes experienced psychological distress, and 50.6% experienced anxiety, indicating a relatively high prevalence of psychological disorders in this population. This study indicated that student-athletes who experience psychological distress are also more likely to feel worried, revealing exactly how impossible it can be to reconcile school and athletics. The findings underscore the particular mental health issues these students confront as they strive to keep up with both their academic and sports commitments. We therefore recommend the importance of integrated psychological interventions and tailored mental health support for student-athletes to help them manage stress and anxiety, as well as improve their academic and athletic performance.